Analysis of the effect of consumer attitude and satisfaction on interest to buy online shopping at Zalora - Wiwin Surtinah (Privietlab, 2022)
This study uses quantitative research aimed to find out and analyze the influence of consumer attitudes on interest in buying products at Zalora, to find out and analyze the effect of consumer satisfaction on interest in buying products at Zalora, to find out and analyze the influence of consumer attitudes and consumer satisfaction on the influence of the number of consumers who make online purchases at Zalora. In this study, researchers used multiple linear regression research methods using the SPSS program so that researchers could find out how the results of the significance level of the influence of consumer attitudes and consumer satisfaction on consumer spending interest in Zalora company. The data collection technique carried out by the researcher was using probability sampling with a random sampling of 54 respondents. This method uses a significance level of 5% or an alpha value of 0.05. The results showed that there was no significant effect between consumer attitudes towards online shopping interest in Zalora , and there was no significant effect between consumer satisfaction and online shopping interest in Zalora . Thus, it can be concluded that there is no significant effect between consumer attitudes and consumer satisfaction on online shopping interest in Zalora.